Chemical Forms of Cu, Zn, Ni and Co in Soil and Sediment of .Ranau, Sabah - Jopony, Marcus (1985)
This study was conducted to determine the distribution of the chemical forms of Cu, Zn, Ni and Co in the soil and sediment samples obtained from Lohan area in Ranau, Sabah. The samples were sequentially extracted with 0.5 M KNO /0 remove soluble plus exchangeable metals, with 0.5 M NaOH to remove organically bound metals, 0.05 M Na zEDTA to dissolve metals in oxide or carbonate form, and with 4 M HNO 3 at 80°C to dissolve metals in sulphide minerals. Most of the metals analysed were present as sulphide minerals with the exchangeable plus soluble fractions being very low.